Diseño de una Propuesta de Red de Calidad del Aire para el Cantón Ambato, Provincia de Tungurahua - Unach (2019)
This research is intended to design a proposal for a network of air quality monitoring in Ambato city, for which was all available information on air quality monitoring in the aforementioned city was collected, as well as information on pollution sources meteorological, topographic and demographic characteristics, which allow the location of monitoring point of stations of network. First, the grid method was applied, which makes a mesh that divide the study area into squares of 1 km on each side. After, these points are assigned to each vertex and a pre-selection is made, discarding the points that are located in bodies of water and unpopulated areas. Through of the multicriteria analysis, the preselection points are filtered against several location criteria and the minimum requirements of the station, obtaining the definitive points of location of the stations. The existence of a single air quality monitoring stations was determined, which works since 2016 measuring four environmental parameters. As a result of the multicriteria analysis, two networks were determined. The first is the optimal monitoring network, which is made up of eleven stations that will allow the identification of the air quality status of the city with the greatest availability of data and the second, the minimum monitoring network that is made up of four stations, with this last, representative data of the air quality in the city will be obtained with a lower investment. In both cases the stations cover the monitoring area effectively.